Entitlement - Alam, Rumaan (Riverhead Books, 2024)
"Brooke Orr is on a mission to change her life and the world. Assisting an octogenarian billionaire in the quest to give away his vast fortune turns out to be deeply satisfying work, a noble life path. All you need to make the world a better place, it turns out, is the right ideals with the right amount of money. She and her billionaire make an uncommon pair: Brooke, 33, is a Black woman raised by a single mother in New York City; Asher Jaffee, 83, is a white business tycoon with an elaborate lifestyle. Each is exhilarated by the new friendship. Asher loves Brooke's willingness to spar with him, and Brooke finds her proximity to Asher's power intoxicating, even mind altering. As limits are increasingly pushed and unusual boundaries crossed, the line between need and want blurs dramatically."--